Pendidikan Karakter Perspektif KH. Ahmad Dahlan dan KH. Hasyim Asy’ari: Sebuah Kajian Komparatif untuk Pengembangan PAI Kontemporer - Jimmy Malintang; Nailil Maziyati; Muhammad Ihsan Siregar; Yaqut Elok Romlah Faiqoh (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Character education in Islamic Religious Education (IRE) needs to be continuously developed so that it does not stop at the mastery of religious material, but is able to shape students who are knowledgeable, virtuous, civilized, and socially responsible. This study aims to analyze the concept of character education from the perspectives of KH. Ahmad Dahlan and KH. Hasyim Asy’ari, identify their similarities and differences, and formulate its relevance for the development of contemporary PAI. This study employs a qualitative approach using a literature review methodology. Data were obtained through the review of primary and secondary literature, such as the works of key figures, academic books, journal articles, and relevant educational documents. Data were analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions and verification. The research findings indicate that KH. Ahmad Dahlan emphasized character education through the integration of faith, knowledge, good deeds, renewal, and social benefit, whereas KH. Hasyim Asy’ari emphasized character education through etiquette, moral conduct, sincerity, and respect for knowledge. The synthesis of these two perspectives yields a PAI character education model that integrates faith, knowledge, good deeds, etiquette, and social responsibility. The implications of this study underscore the need for PAI instruction that is more contextual, reflective, and oriented toward the internalization of values in students’ lives.